PENERAPAN METODE DRILL UNTUK MENINGKATKAN KEMAMPUAN MENYANYIKAN LAGU DAERAHNUSANTARASISWA KELAS V SDN 119 PEKANBARU - Antosa, Zariul Antosa; Marhadi, Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The problem of this research is to improve the ability to sing folk songs archipelago Elementary School fifth grade students 119 Pekanbaru in learning the art of music with the application of the method Drill. Learning the art of music in this school only to learn the material just never do direct practice. This is due to the lack of teacher knowledge about the art of music. In any learning activity, the teacher just use a lecture or explain any material. In learning the art of music performed by lecture method simply makes children become passive in learning. So that the formulation of the problem in this research is: "Does the application of the drill method can improve the ability to sing folk songs archipelago Elementary School fifth grade students 119 Pekanbaru". Subjects in this study were students of class V SDN 119 Pekanbaru academic year 2013/2014 the number of students 25 people. This research was conducted in two cycles, the first cycle held two meetings with one final assessment cycle and cycle II also conducted two meetings and one final assessment cycle. Data collection instruments in this study is observation sheet teacher, student observation sheets, evaluation sheets and sheet product assessment process. The study is in the form of classroom action research (PTK), which aims to increase the area of the archipelago memampuan sing fifth grade students of SDN 119 Pekanbaru on song material archipelago area. The results showed that the application of the drill method can improve the ability to sing folk songs archipelago in learning the art of music students of class V 119 Pekanabaru. On preliminary data the average value of 60.08 in the assessment of students sang folk songs in the first cycle of the average value of 62.2 students increased by 2,12 of initial data. Meanwhile the results of the assessment sing folk songs second cycle students' average score increased to 72.73 increased by 10.53 of the assessment cycle sing folk songs I. This indicates that the application of the drill method can improve the ability to sing folk songs archipelago in learning the art of music students of class V SDN 119 Pekanbaru. Key words: Learning Method Drill, Regional Songs Singing Ability Archipelago